Studi Pertambahan Beban Transformator Daya Pada Gardu Induk Parit Baru PT. PLN (Persero) Cabang Pontianak - ., Syamsul Bahri (Faculty of Engineering, Universitas Tanjungpura, 2015)
ABSTRACT The need for electricity Pontianak continued to rise every year. The fact requires the development and good planning in electric power systems. One of the components in the power system needs to be improved is the power transformer. This is needed because the power transformer plays an important role in distributing electricity to consumers. Based on peak load feeders data fromÂ PT. PLN (Persero) Parit Baru substation Branch Pontianak, it has described the rapid development of load capacity. This resulted in the need for further studies to predict the load at the substation. Increasing the capacity of the power transformer in the substation Parit Baru can be done by calculating the peak load prediction for the current and future. Studies needed to increase the peak load is used to calculate the approximate capacity of power transformer in the substation by using an exponential regression function which has the smallest standard error as compared with the linear regression function. Based on the results of the approximate calculation of the load and by SPLN17A / 79,Â the peak load in 2016 amounted to 30.904 MVA happened already past capacity power transformer substation in Parit Baru and that should be anticipated with the correct solution. Results to be achieved in 2016 is to increase the capacity of power transformer in the Parit Baru substation. Â Keywords: Substation, Power Transformers, Capacity, Peak Load